Avaliação da viabilidade de micro-organismos isolados de grãos de kefir submetidos ao processo de liofilização para formulação de culturas iniciadoras - Karen Costa (2019)
Kefir is a fermented beverage, traditionally made by the inoculation of kefir grains in food matrices, like milk and sugary water. These grains are constituted by a highly diverse microbiota of bacteria and yeast in a symbiotic association. These mixtures of microorganisms present in kefir grains are found surrounded by a matrix which has a polysaccharide nature, known as kefiran. Despite of several studies had demonstrated health benefits with the consumption of kefir, in Brazil the consumption of this beverage is still incipient, and the production is restrict to the domestic environment, with a direct inoculation of the grains in the substrate. This process results in non-standard beverages, with organoleptic and rheological characteristics that could vary depending on the conditions of maintenance and cultivation of the grains. For standardized large-scale production of kefir, it is necessary the use of starter cultures. Therefore, the aim of this research is to evaluate the effect of lyophilization on the viability and the growth pattern of lactic acid bacteria (Lactococcus spp.; Leuconostoc spp.) and yeasts (Saccharomyces spp, Lachancea fermentati) isolated from Brazilian kefir grains, right after the lyophilization process, using sucrose, threalose or skim milk as crioprotectants, and during storage at 5 ± 2 ºC e 25 ± 2 ºC. The use of cryoprotectants in the dehydration process and storage at 5 ± 2 ºC allowed greater survival of the microorganisms to lyophilization. It were selected strains of each gender of acid lactic bacteria and yeast by analysis of the results on the profile of resistance to the process in order to compose formulations of lyophilized starter cultures. For each formulation of the starter culture tested, the physical-chemical (pH, lactic acid, acetic acid and ethanol) and microbiological (viable cells count) characteristics of the beverages made from milk presented characteristics very close to kefir produced with the grains. In addition, the standards required by Brazilian legislation were maintained along 28 days of refrigerated storage. Thus, it was demonstrated that it was possible to produce fermented milk kefir with starter culture, using combinations of lyophilized microorganism isolated from the kefir grains.